Improving Dynamic Archive Security Based Biometric System for Identification and Authentication with Personal Fingerprint - Ifriza, Yahya Nur; Sudarno, Sudarno (Economic Education Analysis Journal, 2021)
Pandemic has impacted many areas of life and led to the development of much new behaviour due to people's efforts to adapt, including adaptation in the workplace. The WFO (Work from Office) and WFH (Work from Home) rules will be enforced during the Covid-19, and this is one of the adaptive steps taken. Some employees are required to work from the office, while others are allowed to work from home under this rule. The author aimed to investigate the development of a microcontroller-based dynamic archive security system to address archive security during the WFH and WFO periods. With security system, the goal was to develop security tools that can serve two functions simultaneously, namely protecting data from loss while making it easier for workers to access the dynamic archives they need. This research was conducted by using research and development methods and the object of research was education staff at the Faculty of Economics, UNNES, using research and development strategies, this study succeeded in making a Dynamic Archive Security System product based on Biometric System Identification. Suggestions in this research on security systems can also be added with variations with RFID cards or NFC cards to implement various security systems.